EFFICIENCY OF DISINFECTION AND STERILIZATION IN DENTAL MEDICINE PRACTICE. REVIEW. - Ionuț-Daniel G; Maria-Alexandra Martu; Oana Butnaru; Iris-Malina Maftei; Ana-Emanuela Botez; Doinita Temelie-Olinici; Ionut-Catalin Botezatu; Carmen Elena Cotrutz (Romanian Dental Association for Education, 2023)
Medical devices that come into contact with sterile tissues or body fluids are considered critical items. In dentistry, conventional manual decontamination of medical device surfaces is used, and this requires a two-step procedure that includes rehydration of the surface followed by decontamination, for effective inactivation of bacteria and viruses on dry surfaces The most effective decontamination agents are ethanol in high concentration while sodium hypochlorite and hydrogen peroxide require a minimum concentration to be effective with little impact on human health. The bactericidal action of quaternaries has been attributed to inactivation of energy-producing enzymes, denaturation of essential cellular proteins, and disruption of the cell membrane. Sterilization destroys all microorganisms on the surface of an item or in a fluid to prevent the transmission of diseases associated with the use of that item Most medical and surgical devices used in medical facilities are made of materials that are heat stable and therefore undergo high temperature sterilization, primarily with steam.